ERUCA SATIVA MILL SEEDS OIL ALLEVIATES HYPERLIPIDEMIA AND NON-ALCOHOLIC FATTY LIVER DISEASE IN SYRIAN HAMSTER - M. Alhilal; Y. A. M. Sulaiman; A. M. Subuh; N. Habra; S. Alhilal (Journal of Animal and Plant Sciences, 2022)
The impact of oils rich in long chain monounsaturated fatty acids (LCMUFA) against hyperlipidemia and non-alcoholic fatty liver disease (NAFLD) has been inadequately described. In addition, the chemical solvents and the high temperature used in vegetable oils extraction process from seeds cause severe loss of many vital compounds. So the goal of this paper was to examine the effect of cold pressed Eruca sativa Mill seeds oil (ESSO), as a source of LCMUFA, on hyperlipidemia and NAFLD in Syrian hamster. The ESSO content of fatty acids was analyzed using chromatographic methods. Fifty two (52) healthy male golden Syrian hamsters used in this experiment were randomly divided into 4 groups (Completely Randomized Design). Negative control group, CHD group, positive control group and ESSO group. This experiment was achieved in two periods. The first period continued 4 weeks, in which hyperlipidemia and NAFLD were induced in CHD, positive control and ESSO groups through feeding on a hyperlipidemic diet. The second period also lasted 4 weeks, in which ESSO was orally gavaged at 2 g/kg of the body weight daily to animals of ESSO group. The levels of total cholesterol (TC), triglycerides, HDL-C and glucose and the activities of ALT, AST, ALP, LDH and CK were analysed in the serum. One way analysis of variance (ANOVA) followed by Duncan's multiple range test was used for statistical analysis. The consumption of hyperlipidemic diet for 4 weeks caused a significant raise (P<0.05) of triglycerides, glucose, ALT, AST, LDH, CK and a significant reduction (P<0.05) of the HDL-C/TC ratio, at the same time created lipid accumulation in liver cells in CHD, positive control and ESSO groups in comparison with negative control group at the end of the first period. These negative influences were alleviated in ESSO group by administration of ESSO at the end of second period. In conclusion, The examined cold pressed ESSO has effective hypolipidemic and hepatoprotective effects in Syrian hamsters with hyperlipidemia and NAFLD.
Keywords: Eruca sativa seeds oil; Hamster; Hyperlipidemia; Non-alcoholic Fatty Liver Disease